Trading food across West African borders - Akoto-Danso, E. K.; Karg, H. (International Water Management Institute, 2022)
West African cities depend also on food imported from the global market and on intra-regional trade to supplement national food supplies. However, barriers on the road and at borders make cross-border trade challenging and expensive. Find out more about cross-border trade in West Africa, the formal and informal barriers, and why traders and transporters of food produced and consumed in the region are affected more by these barriers than others. This documentary summarizes findings from a road trip on a truck from the port in Tema, Ghana, to Ouagadougou, Burkina Faso.